Age-dependent functional crosstalk between cardiac fibroblasts and cardiomyocytes in a 3D engineered cardiac tissue. (June 2017) - Li, Yanzhen; Asfour, Huda; Bursac, Nenad
Graphical abstract: Abstract: Complex heterocellular interactions between cardiomyocytes and fibroblasts in the heart involve their bidirectional signaling via cell-cell contacts, paracrine factors, and extracellular matrix (ECM). These interactions vary with heart development and pathology leading to changes in cardiac structure and function. Whether cardiac fibroblasts of different ages interact differentially with cardiomyocytes to distinctly impact their function remains unknown. Here, we explored the direct structural and functional effects of fetal and adult cardiac fibroblasts on cardiomyocytes using a tissue-engineered 3D co-culture system. We show that the age of cardiac fibroblasts is a strong determinant of the structure, function, and molecular properties of co-cultured tissues. In particular, in vitro expanded adult, but not fetal, cardiac fibroblasts significantly deteriorated electrical and mechanical function of the co-cultured cardiomyocytes, as evidenced by slower action potential conduction, prolonged action potential duration, weaker contractions, higher tissue stiffness, and reduced calcium transient amplitude. This functional deficit was associated with structural and molecular signatures of pathological remodeling including fibroblast proliferation, interstitial collagen deposition, and upregulation of pro-fibrotic markers. Our studies imply critical roles of the age of supporting cells in engineering functional cardiac tissues and provide a new physiologically relevant in vitro platform to investigate influence of heterocellular interactions on cardiomyocyte function, development, and disease. Statement of Significance: Previous studies have shown that cardiomyocytes and fibroblasts in the heart interact through direct contacts, paracrine factors, and matrix-mediated crosstalk. However, whether cardiac fibroblasts of different ages distinctly impact cardiomyocyte function remains elusive. We employed a tissue-engineered hydrogel-based co-culture system to study interactions of cardiomyocytes with fetal or adult cardiac fibroblasts. We show that the age of cardiac fibroblasts is a strong determinant of the structure, function, and molecular properties of engineered cardiac tissues and that key features of fibrotic myocardium are replicated by supplementing cardiomyocytes with expanded adult but not fetal fibroblasts. These findings relate to implantation of stem cell-derived cardiomyocytes in adult myocardium and warrant further studies of how age and source of non-myocytes impact cardiac function and maturation.